KNOWLEDGE, ATTITUDE AND PRACTICES ON NOSOCOMIAL INFECTION PREVENTION AND CONTROL AMONGST HEALTH WORKERS IN MUBENDE REGIONAL REFERRALHOSPITAL, MUBENDE DISTRICT. A CROSS-SECTIONAL STUDY. - BAYIYANA , MAZZI JULIET; NAMUTEBI , FLORENCE (Student's Journal of Health Research Africa, 2024)
Background Nosocomial infection rates are still high and have rather steadily increased during the recent decade, this can be due to the carelessness of health workers, failure to observe and adopt standard operating procedures, and poor waste segregation and disposal. This study aims to assess the knowledge attitude and practices on nosocomial infection prevention and control among health workers in Mubende Regional Referral Hospital, Mubende district Methodology A descriptive cross-section study employing a quantitative method was used, where 50 participants were selected using a simple random sampling method, data was collected using semi-structured questionnaires, and results were entered into the computer data program and Microsoft Excel for frequency tables Results 60% mentioned that blood-borne infections are the most commonly occurring born infections, and 78% of the respondents said patients were the most common sources of hospital-acquired infections to health workers. 80% of respondents thought working in a hospital exposes you to infection with 60% thinking that his /her family members may get infected through him because some infections can be obtained from contacts and 78% of respondents felt that using PPE is essential and it can prevent the occurrence of nosocomial infections 40% were washing hands before aseptic procedures, and the majority 80% after touching the patient environment, 60% of the respondents disposed of their medical wastes and biohazards wastes after segregation and 80% discarded there sharps in the safety box, and the least 4%in bins. Conclusion Health workers in this study had sufficient knowledge of infection prevention prevention, but their attitudes and implementations of safe practices were substandard. The healthcare healthcare workers' practices were unsatisfactory. Recommendation Health workers should be trained through continuous medical education, going for further training to improve their knowledge of nosocomial infection control in health facilities